ALIGNING TEACHING AND LEARNING PRACTICES IN CHILDCARE CENTRES WITH THE ASPIRATIONS OF TODAY'S PARENTS: A FOCUS ON INFANTS AND TODDLERS: A CASE STUDY - NURUL FATIHAH SABRY; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study examines the implementation of a teaching and learning approach (PdP) for children enrolled in TASKA that can meet the aspirations of today's parents. The aspirations include safety, holistic development, fun learning, close communication between parents and educators, and controlled use of technology. Data was collected through the analysis of articles and research reports published between 2020 and 2025. The results of the study found that the most effective approach is play-based learning, child-centered learning, sensory experiences, consistent daily routines, parental involvement, and limited use of technology. Although this approach is in line with the developmental needs of children with disabilities, its implementation faces challenges such as lack of resources, trained workforce, and physical facilities. This study recommends that TASKA provide specific training to educators, improve communication with parents, and improve the learning environment to make it safer and more child-friendly.